Benthenic macroinvertebrates as bioindicators of water quality in a climate change scenario: a systematic review (Revista Espinhaço, 2024)
The increasing anthropogenic changes in the terrestrial environment reflect significant impacts on freshwater ecosystems. One of the most efficient ways to carry out a diagnosis of the “health” of a given water body is through the use of water quality bioindicators, which we call benthic macroinvertebrates. These organisms quickly and accurately reflect minimal changes to aquatic environments due to their sensitivity to various types of pollutants and physical disturbances, in addition to being an essential component for the functioning and balance of aquatic ecosystems, acting in ecological processes of energy transfer and nutrient cycling. The present study aimed to carry out a systematic review of scientific works published on the Scopus platform in the last 10 years, evaluating the use of benthic macroinvertebrates as a biomonitoring tool for monitoring water quality, in the context of climate change. Of the 254 works sampled, only four were related to the study proposal, demonstrating an important knowledge gap to be explored in the coming years.
Keywords: biomonitoring; benthic communities; global changes